Sex Differences Associated with Primary Biliary Cirrhosis - Daniel S. Smyk; Eirini I. Rigopoulou; Albert Pares; Charalambos Billinis; Andrew K. Burroughs; Luigi Muratori; Pietro Invernizzi; Dimitrios P. Bogdanos (Clinical and Developmental Immunology)
Primary biliary cirrhosis (PBC) is a cholestatic liver disease of autoimmune origin, characterised by the destruction of small intrahepatic bile ducts. The disease has an unpredictable clinical course but may progress to fibrosis and cirrhosis. The diagnostic hallmark of PBC is the presence of disease-specific antimitochondrial antibodies (AMA), which are pathognomonic for the development of PBC. The disease overwhelmingly affects females, with some cases of male PBC being reported. The reasons underlying the low incidence of males with PBC are largely unknown. Epidemiological studies estimate that approximately 7–11% of PBC patients are males. There does not appear to be any histological, serological, or biochemical differences between male and female PBC, although the symptomatology may differ, with males being at higher risk of life-threatening complications such as gastrointestinal bleeding and hepatoma. Studies on X chromosome and sex hormones are of interest when studying the low preponderance of PBC in males; however, these studies are far from conclusive. This paper will critically analyze the literature surrounding PBC in males.